Inhibition mechanism of human salivary α-amylase by lipid transfer protein from Vigna unguiculata. (April 2020) - da Silva, Flávia Camila Vieira; Pessoa Costa, Evenilton; Moreira Gomes, Valdirene; de Oliveira Carvalho, André
Graphical abstract: Highlights: HSA is inhibited by Vu LTP1.1 because the obstruction of the carbohydrate biding cleft. Vu LTP1.1 Arg39 is burrowed into the active site of the HSA. Vu LTP1.1 Arg39 interacts with the Asp300 of HSA catalytic site by a hydrogen bond. Abstract: Vu LTP1.1, a LTP1 from Vigna unguiculata, inhibits 78.1 % of the human salivary α-amylase (HSA) activity at 20 μM. We had performed a correlation study between Vu LTP1.1 structure and HSA inhibitory activity and showed that two Vu LTP1.1 regions are responsible for HSA inhibition. In one of them we had characterized the crucial importance of an Arg39 for inhibition. In this work, we analyzed the Vu LTP1.1-HSA interaction by protein-protein docking to understand the most probable interaction model and the mechanism of HSA inhibition by Vu LTP1.1. The Vu LTP1.1 tertiary structure quality and refinement as well as the docking assay between Vu LTP1.1 and HSA were done by bioinformatic programs. HSA inhibition occurs by direct interaction of the Vu LTP1.1 with the HSA causing the obstruction of the carbohydrate biding cleft with Gibbs free energy of -18.5 Kcal/mol and the dissociation constant of 2.6E −14 M. The previously identified Arg39 of Vu LTP1.1 is burrowed into the active site of the HSA and there it interacts with the Asp300 of HSA catalytic site by a hydrogen bond. We had confirmed the importance of the Arg39 of Vu LTP1.1 for the HSA inhibition which interacts with the Asp300 at the HSA active site. I-2, a LTP-like peptide, presents the same HSA inhibition pattern that Vu LTP1.1, which indicates that the inhibition mechanism of the LTPs towards α-amylase is very similar. For the best of our knowledge, it is the first time that the HSA inhibition mechanism was understood and described for the LTP1s using Vu LTP1.1 and I-2 as prototype inhibitors.